Strategi Peningkatan Brand Loyalty dan Customer Satisfaction Bisnis Yogurt di Indonesia (Studi Kasus: PT Yummy Food Utama) - Indana Saramita Rachman; Aida Vitayala S Hubeis; Suryani Sidik F Motik (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2017)
The objectives of this study were to analyze the key success factors of the yogurt business and recommend strategies to increase brand loyalty and customer satisfaction at PT Yummy Food Utama. The method used in this research was descriptive analysis method with case study approach at PT Yummy Food Utama with descriptive analysis, PESTEL framework, and Porter’s five forces. The result of descriptive analysis shows that the key success factors of yogurt business at PT Yummy Food Utama in terms of the behavior of the importance of consuming yogurt, accessibility products, and acceptability of the products are understanding the benefits of consuming yogurt, brand loyalty and product quality while the result of PESTEL framework and Porter’s five forces shows the strategies that has to be done by PT Yummy Food Utama on brand loyalty and customer satisfaction are retaining and maintaining the quality of products, educating the public and delivering the benefits of the importance of consuming yogurt, increasing the popularity of the product through the promotion by using electronic media (television advertising), establishing communication with consumers, opening up a free hotline "24 hours 7 days" and reproducing the flavors of products.Keywords: yoghurt, key success factor, brand loyalty, customer satisfaction, PESTEL framework, Porter’s Five ForcesABSTRAKPenelitian in bertujuan menganalisis faktor kunci keberhasilan dari bisnis yogurt dan merumuskan strategi untuk meningkatkan brand loyalty dan customer satisfaction pada PT Yummy Food Utama. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dalam bentuk studi kasus pada PT Yummy Food Utama dengan menggunakan analisis deskriptif, kerangka PESTEL dan Porter’s five forces. Hasil analisis deskriptif menunjukkan faktor-faktor kunci keberhasilan bisnis yogurt PT Yummy Food Utama ditinjau dari perilaku pentingnya mengkonsumsi yogurt, aksessibilitas produk dan akseptabilitas produk adalah pemahaman manfaat mengkonsumsi yogurt, brand loyalty dan kualitas produk. Sedangkan dari hasil analisis PESTEL dan Porter’s Five Forces menunjukkan strategi yang harus dilakukan oleh PT Yummy Food Utama dalam meningkatkan brand loyalty dan customer satisfaction antara lain: mempertahankan dan menjaga kualitas produk, mengedukasi masyarakat dan menyampaikan manfaat akan pentingnya mengkonsumsi yogurt, meningkatkan popularitas produk melalui media promosi elektronik (iklan di televisi), membangun komunikasi dengan konsumen, membuka hotline gratis “24 jam 7 hari” dan memperbanyak varian rasa produk.Kata kunci: yogurt, faktor kunci keberhasilan, brand loyalty, customer satisfaction, PESTEL, Porter’s five forces.